Leading in the Interim: Navigating Interim Chair Appointments - Patricia L. Bullock Ph.D.; L Lynn Stallings Ph.D.; Traci Redish Ph.D.; Diana Gregory Ph.D.; R. Ugena Whitlock Ph.D. (Academic Chairpersons Conference Proceedings, 2016)
In this session, four former interim chairs and one current interim chair will discuss navigating the role of interim chair, and will make recommendations on topics including navigating the first few days of the appointment, evaluating faculty, working with the Dean, and making curricular or policy changes.
Keywords: · leading change; redefining the department; New chairs; Interim; transitions